Real-World Evidence on the Sensitivity of Preoperative Ultrasound in Evaluating Central Lymph Node Metastasis of Papillary Thyroid Carcinoma - Yao, Fan; Yang, Zhongyuan; Li, Yixuan; Chen, Weichao; Wu, Tong; Peng, Jin; Jiao, Zan; Yang, Ankui (Frontiers in Endocrinology, 2022)
Introduction Guidelines for prophylactic dissection in clinical central negative node (cN0) of papillary thyroid carcinoma vary among different countries due to the uncertainty on the benefit of dissection. The Chinese guidelines recommend prophylactic central compartment lymph node dissection (pCLND) under professional technology. Preoperative ultrasound (US) evaluation of central lymph node determines the surgical strategy used. Sensitivity differs significantly when US is conducted by different physicians even in diverse hospitals. In this study, the aim was to explore why the Chinese guidelines were different from the America Thyroid Association (ATA) guidelines through the real-world evidence on the preoperative diagnosis of cN0. Methods Preoperative US and surgical pathology data for 1,015 patients with PTC attending 13 Grade-A tertiary hospitals in 2017 were collected. A retrospective analysis using US assessment of CLNM was the conducted to explore the benefits of this approach in China. US physicians in our hospital were trained on scanning the thyroid gland and its regional lymph nodes in normalization. Data of 1,776 patients were collected under the same condition from 2012 to 2017, whose ultrasonography was performed by diverse physicians and doctors. Further, data of 339 patients evaluated by the same sonographer and operated by the same surgical team was collected between 2015 and 2017. In this set of data, US combined CT versus US alone was compared. Patients were grouped into metastasis group and non-metastasis group based on postoperative pathological diagnosis of CLNM. Diagnostic efficacy of US was evaluated. Results A total of 925 patients who underwent preoperative ultrasonography in central lymph node, including 825 cases who underwent thyroidectomy and central lymph node dissection were included in this study. The sensitivity of ultrasonography in detecting CLNM was 23.18%, with occult metastasis rate of 40.8%. Data for 1,776 patients comprising paired ultrasonic report and pathological report were collected in our hospital, whose physicians underwent standardized training. The sensitivity was 37.58%. Furthermore, specialized evaluation showed high sensitivity in US/CT (84.58%) than US (58.21%) alone. Conclusion Although the sensitivity of US could be enhanced by standardized training and combination with CT, the prevalence of low sensitivity of US in real-world multicenter data and the high occult metastasis rate indicated that the Chinese guidelines were based on the current conditions.